Galectin-8 induces partial epithelial–mesenchymal transition with invasive tumorigenic capabilities involving a FAK/EGFR/proteasome pathway in Madin–Darby canine kidney cells - Oyanadel, Claudia (Mol Biol Cell, 2018)
Epithelial cells can acquire invasive and tumorigenic capabilities through epithelial–mesenchymal-transition (EMT). The glycan-binding protein galectin-8 (Gal-8) activates selective β1-integrins involved in EMT and is overexpressed by certain carcinomas. Here we show that Gal-8 overexpression or exogenous addition promotes proliferation, migration, and invasion in nontumoral Madin–Darby canine kidney (MDCK) cells, involving focal-adhesion kinase (FAK)-mediated transactivation of the epidermal growth factor receptor (EGFR), likely triggered by α5β1integrin binding. Under subconfluent conditions, Gal-8–overexpressing MDCK cells (MDCK-Gal-8(H)) display hallmarks of EMT, including decreased E-cadherin and up-regulated expression of vimentin, fibronectin, and Snail, as well as increased β-catenin activity. Changes related to migration/invasion included higher expression of α5β1 integrin, extracellular matrix-degrading MMP13 and urokinase plasminogen activator/urokinase plasminogen activator receptor (uPA/uPAR) protease systems. Gal-8–stimulated FAK/EGFR pathway leads to proteasome overactivity characteristic of cancer cells. Yet MDCK-Gal-8(H) cells still develop apical/basolateral polarity reverting EMT markers and proteasome activity under confluence. This is due to the opposite segregation of Gal-8 secretion (apical) and β1-integrins distribution (basolateral). Strikingly, MDCK-Gal-8(H) cells acquired tumorigenic potential, as reflected in anchorage-independent growth in soft agar and tumor generation in immunodeficient NSG mice. Therefore, Gal-8 can promote oncogenic-like transformation of epithelial cells through partial and reversible EMT, accompanied by higher proliferation, migration/invasion, and tumorigenic properties.